AN ANALYSIS OF STUDENTS’ ETHICS IN ONLINE LEARNING PROCESS - Ade Aini Nuran (BAHAS, 2020)
Abstract Ethics in the learning process is the relationship between teacher and student involvement that affects the learning process to run smoothly. In this pandemic covid-19 era, all activities are done by online, both in the world of work and education, including teaching and learning activities at schools and universities. Students and teachers have various complaints related to the online teaching and learning process. This research conducted by using quantitative descriptive, which the instrument is questioner contains 10 questions, and the sample is 42 college students randomly. The objective of this study to identify students' ethics in online learning process and the result revealed all the aspects to examine students’ ethics are still normal as well as in classroom which almost all students still wear polite clothes, pay attention to the teacher, active in learning, discipline, responsive, take a note about teachers explanation.Keywords: Ethics, Student, Online Learning Process.